PENGGUNAAN GAYA BAHASA DALAM DEBAT CAPRES TAHUN 2024 - Ahmad Fathur Rosi; Usrin Malikha (SulukAksara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to analyze the use of rhetorical styles in the 2024 presidential debates in Indonesia. In a political context, presidential debates are crucial moments where candidates present their vision, mission, and ideologies to the public. This research focuses on how candidates use rhetorical styles to express their views, respond to current issues, and persuade the public of their leadership capabilities. The study employs a qualitative method with descriptive analysis to examine the types of rhetorical styles used, such as satire, sarcasm, and others. Additionally, it explores how arguments are constructed during the debates. The results indicate that the rhetorical styles used by the candidates play a significant role in shaping public perception and political dynamics. Negative rhetorical styles tend to exacerbate polarization and can harm the candidate’s image, while positive and constructive rhetorical styles can enhance public support.This study is expected to contribute to the development of linguistic sciences and provide insights into effective political communication strategies. Furthermore, it offers valuable feedback for political practitioners and the general public in understanding the importance of using proper and effective language in political contexts.